2020
DOI: 10.3390/pr8121637
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Ethanol Concentration in Costal Cartilage in Relation to Blood and Urine

Abstract: Blood is not always available in forensic autopsies, therefore, the search for alternative sampling materials is needed. This study aimed at examining if ethanol can be detected in costal cartilage and to investigate if different forms of costal cartilage can give accurate information about ethanol concentration in the blood or urine of human cadavers (n = 50). Ethanol concentration in samples of unground costal cartilage (UCC), ground costal cartilage (GCC), femoral venous blood, and urine was analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The ethanol concentration ratio between the blood and urine of the deceased with the confirmed ethanol intoxication was 0.83, 0.89, and 0.70, respectively for Case 1, Case 3, and Case 6. Our earlier study on unembalmed cadavers (n = 39) showed that the average blood/urine ethanol concentration ratio was 0.85  0.24 [25]. The comparative analysis showed that the average blood/urine ethanol concentration ratio for unembalmed cadavers [25] does not differ from the values obtained for presented Case 1 and Case 3 (p = 0.669 and p = 0.286, respectively) but is higher than in presented Case 6 (p < 0.001), which most probably results from the longer time interval between the time of death and the time of the toxicological analyses.…”
Section: Discussionmentioning
confidence: 96%
“…The ethanol concentration ratio between the blood and urine of the deceased with the confirmed ethanol intoxication was 0.83, 0.89, and 0.70, respectively for Case 1, Case 3, and Case 6. Our earlier study on unembalmed cadavers (n = 39) showed that the average blood/urine ethanol concentration ratio was 0.85  0.24 [25]. The comparative analysis showed that the average blood/urine ethanol concentration ratio for unembalmed cadavers [25] does not differ from the values obtained for presented Case 1 and Case 3 (p = 0.669 and p = 0.286, respectively) but is higher than in presented Case 6 (p < 0.001), which most probably results from the longer time interval between the time of death and the time of the toxicological analyses.…”
Section: Discussionmentioning
confidence: 96%
“…Femoral blood and urine samples were collected as described in forensic guidelines [32]. Analyses of ethanol, acetone, and isopropanol levels in these samples were estimated using procedures developed by Tomsia et al [33].…”
Section: Sample Preparationmentioning
confidence: 99%
“…The carrier gas was helium (5.0 mL/min), and t-butyl alcohol was used as an internal standard. The validation procedures for isopropanol and acetone analysis in GCC and UCC were done the same way as the validation procedure for ethanol presented in the study by Tomsia et al [33].…”
Section: Volatile Substance Analysismentioning
confidence: 99%
“…These guidelines date back to 2012 and have not been updated since, despite suggestions that they are now outdated and need to be revised [4]. It is also worth mentioning that there is a large amount of ongoing research into the potential use of alternative biological specimens in toxicological analysis, including although not limited to the use of costal cartilage in the post-mortem diagnosis of ethyl alcohol intoxication [5]. The advantages, disadvantages, and possibility of using CSF as an alternative biological specimen have been recently reviewed [6].…”
Section: Introductionmentioning
confidence: 99%